Rebalancing power relationships in research using visual mapping: examples from a project within an Indigenist research paradigm. Issue 1 (2nd January 2019) - Lindblom, Anne
ABSTRACT: Engaging in respectful relationships is an essential aspect of all research and educational practices. Colonial residue, and the maltreatment and misinterpretation of Indigenous peoples by researchers, puts a great responsibility on the researcher to strive for balance in power relationships within Indigenous contexts. Even more so, in research and education involving Indigenous children diagnosed with autism spectrum disorder (ASD). This may be easier said than done. In a PhD project on the meaning of music for First Nations children diagnosed with ASD in British Columbia, Canada, visual mapping was used to rebalance the power relationships between myself as a researcher and the research partners as a step toward decolonization. The visual maps were used to summarize conversation transcripts that could be used to validate my interpretations and disseminate the research results, create a mutual focal point for negotiating consent and participation and show progress over time. Visual methods, such as visual mapping, are beneficial to individuals with autism, and can also be useful when rebalancing power relations with other research partners, such as parents. In conclusion, visual mapping can be a useful tool for rebalancing power relationships in research and educational practices.